Monocytes of patients with unstable angina express high levels of chemokine and pattern-recognition receptors - Justo-Junior, A.S.; Villarejos, L.M.; Lima, X.T.V.; Nadruz, W.; Sposito, A.C.; Mamoni, R.L.; Abdalla, R.; Fernandes, J.L.; Oliveira, R.T.D.; Blotta, M.H.S.L. (Cytokine (Philadelphia, Pa.), 2019)
•The phenotypes of monocyte subsets differ at different stages of atherosclerosis.•UA patients exhibit an increased frequency of chemokine receptors and PRRs.•This increased frequency is seen mainly in intermediate monocytes of UA patients.•HSP60 induces IL-12p70 production in intermediate monocytes from control subjects. Macrophages derived from monocytes play an important role in atherosclerosis progression. Subpopulations of circulating classical, intermediate, and non-classical monocytes possess distinct functions and phenotypes, and participate in the pathogenesis of disease. The aim of this study was to compare the quantity and phenotypes of circulating monocyte subpopulations in patients with established atherosclerosis and healthy control individuals. Additionally, the study aimed to provide insight into the functional activity of monocytes against a heat shock protein (HSP60). Chemokine and pattern recognition receptors in monocyte subsets obtained from peripheral blood of acute and chronic coronary artery disease patients and controls were quantified by flow cytometry. Furthermore, monocytes from healthy controls were stimulated in vitro with HSP60, and the cytokines produced by them were evaluated by flow cytometry. Eighteen controls (C), 34 individuals with risk factors for cardiovascular disease (RF), 32 patients with stable angina (SA), and 16 patients with unstable angina (UA) were enrolled in the study. The absolute count of intermediate monocytes was found to be increased in patients of the UA group; high frequencies of the chemokine receptors CCR2, CCR5, and CX3CR1 were also observed in this subpopulation. Moreover, the pattern recognition receptors TLR2 and TLR4 were more frequent in intermediate monocytes from the UA group. Furthermore, the intermediate monocytes from healthy individuals produced IL-12p70 after stimulation with HSP60. Our results show that intermediate monocytes of UA patients exhibited an enhanced expression of the receptors involved in the recognition of damage-associated molecular patterns (DAMPs) and enhancement of the migratory function. Hence, they might contribute to the propagation and progression of inflammation observed in atherosclerosis, especially in the acute setting.